Ti-doped In2O3 transparent conductive thin films with high transmittance and low resistivity - Song, Zhenyu; Fu, Qiang; Li, Lei; Li, Li; An, Yupeng; Wang, Yiding (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Ti-doped In2O3 thin films have been prepared on glass substrate by radio frequency (RF) sputtering with different sputtering powers (90, 120, 150, and 180 W) at 330 °C. The influence of sputtering power on the structural, electrical and optical properties of the deposited thin films is investigated. The average transmittance of the thin films in the wavelength range of 500–1100 nm is over 90%. Low resistivity of 7.3×10–4 Ωcm is also obtained based on our thin films, suggesting that Ti-doped In2O3 is a good candidate for transparent conductive thin film.
Optica Applicata, Vol. 40, 2010, nr 4, s. 751-757
Keywords: optyka; sputtering; In2O3; transparent conductive oxide; thin films